Weak Sensitizers May Be Associated with CD80 Polymorphisms: Implications for Systemic Contact Dermatitis - Susan Nedorost; Ge Zhang; Desta Fekedulegn; Kara Fluharty; Wei Wang; Bonnie Frye; Elma Baron; Kathryn Zug; Berran Yucesoy (JID Innovations)
Chronic irritant dermatitis predisposes to Th2 skewed allergic contact dermatitis. Chronic hand dermatitis due to wet work or childhood- onset irritant flexural dermatitis (AD) is associated with sensitization to weak or non-sensitizing antigens as defined by the local lymph node (LLN) assay. In about 15% of these patients, ingestion of allergens results in systemic contact dermatitis, defined as recall dermatitis at previous sites. In this large exploratory study, not even known associations (e.g. IL4R and AD) survived correction for tests of multiple associations. As such, we analyzed for associations using p<0.005 combined with OR >1.8 or <0.5. We found that positive patch tests to weak allergens were common with 3 polymorphisms of CD80. CD80 is a co-stimulatory molecule on several cell types including innate lymphoid group 2 cells (ILC2). ILC2 presentation may bypass education in the local lymph node, explaining the association of antigens classified as non-sensitizers in LLN assay with CD80, and the absence of symptoms of immediate type hypersensitivity in many of these patients. Food handlers with hand dermatitis and patients with atopic dermatitis should be patch tested to allergens in foods (e.g. propylene glycol, vanillin, nickel, cobalt, and chromates) and instructed on dietary restriction of these allergens.